Problematika Kelompok Kerja dalam Proses Pengumpulan dan Pemutakhiran Data Sustainable Development Goals (SDGs) Desa Tambakrejo, Kecamatan Gurah, Kabupaten Kediri - syafira, qorina aulya; Warsono (Kajian Moral dan Kewarganegaraan, 2024)
Villages as the smallest aspect of a country have a very significant role in the Sustainable Development Goals (SDGs) program. This study aims to identify problems that occur in the process of collecting and updating Sustainable Development Goals (SDGs) data in Tambakrejo Village as well as efforts made by working group volunteers to overcome problems in the SDGs data collection process. The informants in this study are village heads, village secretaries, government heads, village admins, and data collection enumerators who are members of a data collection working group for the SDGs of Tambakrejo Village. The data collection technique uses semi-structured in-depth interviews and documentation. The data obtained was analyzed using Edward III's Policy Implementation Theory. The results of this study show that there are problems faced by volunteers in collecting and updating Tambakrejo Village SDGs data, including the lack of enumerator competence in communicating with the community. The absence of coordination between villages makes it difficult to collect data on mutated residents, and low village commitment results in data not being updated thoroughly. Limited resources, including network constraints, and application maintenance, are also obstacles, plus the double burden faced by enumerators who also serve as PKK cadres. In addition, filling out complicated forms as part of standard operating procedures (SOPs) and unsynchronized data resulted in inaccurate targets in providing assistance.